Healthcare Resource Utilization Associated with Leukopenia and Neutropenia in Kidney Transplant Recipients Receiving Valganciclovir in the United States - Qinghua Li; Vladimir Turzhitsky; Pamela Moise; Harry Jin; Kaylen Brzozowski; Irina Kolobova (Journal of Health Economics and Outcomes Research)
# Background Cytomegalovirus prophylaxis in kidney transplant recipients (KTRs) is limited by post-transplant neutropenia and leukopenia (PTN/PTL). Despite its clinical significance, the healthcare resource utilization (HCRU) related to PTN/PTL remains poorly characterized.